Educational levels as a catalyst for socio-economic development: Observations from human resources viewpoints in sustainable community growth - Hübel (Anghel), Ștefania-Rodica; Stan, Mari-Isabella; Tasențe, Tănase (Technium Sustainability, 2023)
This study explores the complex relationship between education and socio-economic development in a post-pandemic context, highlighting education as a transformative cornerstone. Research shows that improving education has direct and indirect social benefits, including promoting business development and reducing poverty in communities. In addition, education has a significant impact on governance and sustainable development, playing a key role in wider socio-economic transformation and sustainability. Research objectives include assessing the impact of education on life satisfaction, economic stability, prospects, and household income adequacy. A diverse group of 216 participants from Central Dobrogea, Romania, ranging from primary to postgraduate levels of education and representing both the public and private sectors, participated. Education is emerging as a linchpin of national development, particularly in the post-pandemic era where human resources are paramount. It serves as a foundation for promoting sustainable community growth and has a profound impact on an individual’s life satisfaction, prospects, and resilience to crises. The positive correlation between higher educational attainment and increased life satisfaction underscores the indispensability of education in shaping human resource policies for sustainable development. In addition, education equips individuals with the tools to manage post-crisis recovery and fosters optimism for the future. In essence, education acts as an indispensable catalyst for socio-economic progress, providing a pathway for individual growth and the promise of collective progress, resilience, and seizing opportunities in the midst of adversity.